The significance of Podcasting for EFL learning - Fachriza, Aries; Virgiyanti, Diska Fatima; Nuraini, Eka Indah; Dipta, Dinar; Luthfi, Mohammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The use of podcasts as language teaching and learning has obtained more attention today. Podcasts have been used mostly to improve students' listening skill that is proven by numerous studies to determine how podcasts might assist students in improving their listening skills. Whereas, podcasting promotes activities for the students to practice their whole English skills. This is a literature research that provides a review of podcasting to assist EFL learners in mastering English. As many as 20 articles were used as the data sources in arranging this article. The researchers searched the articles using the keywords ‘podcast’ and ‘podcasting’. The difference between this article among previous studies is the focus on the use of podcasting for EFL learnings. The previous studies mostly discussed podcasts and podcasting for improving listening ability. The review found that podcasting is an interesting medium to be used in English learning. However, several challenges arise such as lack of technological competence, lack of vocabulary and grammar, unstable internet connection, and limited facilities. Consequently, it is advised that when using podcasts, teachers give their students appropriate direction on how to maximize their potential.